2008
DOI: 10.1002/kin.20386
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on kinetics of an aromatic nucleophilic substitution reaction in mixtures of an ionic liquid with molecular solvents and prediction using artificial neural networks

Abstract: Kinetics of the reaction between 1-chloro-2,4-dinitrobenzene and aniline was studied in mixtures of [EtSO 4 ]) with methanol, chloroform, and dimethylsulfoxide at 25 • C. Single-parameter correlations of log k A versus normalized polarity parameter (E N T ), hydrogen-bond acceptor basicity (β), hydrogen-bond donor acidity (α), and dipolarity/polarizability (π * ) of media do not give acceptable results. Multiparameter linear regression (MLR) of log k A versus the solvatochromic parameters demonstrates that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…In general, these parameters constitute more comprehensive measures of solvent polarity than the dielectric constant alone, because they reflect more reliably the complete picture of all intermolecular forces acting between solute and solvent molecules. This approach has been widely and successfully applied in the correlation analysis of all kinds of solvent-dependent processes [ 52 56 ]. Using the solvatochromic parameters π *, α , and β , where π * is the index of the solvent dipolarity/polarizability, which is a measure of the ability of a solvent to stabilize a charge or a dipole by its own dielectric effects.…”
Section: Resultsmentioning
confidence: 99%
“…In general, these parameters constitute more comprehensive measures of solvent polarity than the dielectric constant alone, because they reflect more reliably the complete picture of all intermolecular forces acting between solute and solvent molecules. This approach has been widely and successfully applied in the correlation analysis of all kinds of solvent-dependent processes [ 52 56 ]. Using the solvatochromic parameters π *, α , and β , where π * is the index of the solvent dipolarity/polarizability, which is a measure of the ability of a solvent to stabilize a charge or a dipole by its own dielectric effects.…”
Section: Resultsmentioning
confidence: 99%
“…The study of solvent effects in ANS contributes to the understanding of the microscopic properties of solvent due the complex interactions between the amine, the substrate, and/or the intermediate that occur involving the solvent molecules [12][13][14]. Intense research on the differential effects of mixed solvents is also being carried out at present [3, 15,16], and it has been reported that properly selected and trained neural network could fairly represent the dependence of the reaction rate constant on solvatochromic parameters [17]. On the other hand, self-association of amines by hydrogen bonding interactions in nonpolar aprotic solvents is a long known phenomenon [18].…”
Section: Introductionmentioning
confidence: 99%
“…In continuing our investigations about nanomaterial preparations [46][47][48][49] and RTILs [50][51][52][53][54], the ultrasonic-assisted aqueous room temperature ionic liquid (UARTIL) method was applied for preparation of SnO 2 nanoparticles. For above mentioned reasons, halide-free RTIL, 1-ethyl-3-methylimidazolium ethyl sulfate ([EMIM][EtSO 4 ]), was used in this work [55].…”
Section: Introductionmentioning
confidence: 99%